A shift from membranous and stromal syndecan‐1 (CD138) expression to cytoplasmic CD138 expression is associated with poor prognosis in breast cancer. Issue 12 (23rd September 2019) - Kind, Simon; Jaretzke, Annika; Büscheck, Franziska; Möller, Katharina; Dum, David; Höflmayer, Doris; Hinsch, Andrea; Weidemann, Sören; Fraune, Christoph; Möller‐Koop, Christina; Hube‐Magg, Claudia; Simon, Ronald; et al.
Abstract: Syndecan‐1 (CD138) is a transmembrane proteoglycan expressed in normal and malignant tissues. It is of interest because of a possible prognostic effect in tumors and as a target for Indatuximab, a monoclonal antibody coupled to a cytotoxic agent. To assess the prognostic role of CD138 expression in breast cancer (BCa), a tissue microarray containing 1535 BCa specimens was analyzed by immunohistochemistry. Cytoplasmic, membranous, and stromal CD138 staining was separately analyzed. In normal breast tissue, CD138 staining was limited to epithelial cell membranes. In cancers, membranous staining tended to become weaker or even disappeared (38.3% of cancers with absence of membranous staining) but cytoplasmic and stromal staining newly appeared in 29.7% and 58.1% of cancers. Loss of membranous epithelial CD138 staining as well as presence of cytoplasmic and stromal CD138 positivity were—to a variable degree—associated with high pT, high grade, nodal metastasis, estrogen receptor‐negative, progesterone receptor‐negative, human epidermal growth factor receptor 2+, and poor overall patient survival. A combined analysis of epithelial and stromal CD138 expression revealed a link to overall patient survival ( P < .0001) with best prognosis for patients with stromal positivity and absence of cytoplasmic staining, the worst prognosis for cancers with cytoplasmic staining and stromal negativity and intermediate prognosis for patients having either cytoplasmic staining or stromal negativity. In multivariate analyses, CD138 was not independent of established prognostic features. In summary, these data reveal a compartment depending prognostic effect of CD138 expression in BCa with cytoplasmic positivity being linked to aggressive cancer and stromal CD138 being linked to a more favorable prognosis.